Laughing back at empire : the grassroots activism of The Asianadian, 1978-1985 - Wong, Angie (University of Manitoba Press, 2023)
"Asian Canadian activism, resistance, and art of the 1970s and 80s Laughing Back at Empire is a groundbreaking examination of The Asianadian, one of Canada's first anti-racist, anti-sexist, and anti-homophobic magazines. Over the course of its seven-year run, the small but mighty magazine led a nation-wide dialogue for all Canadians on the struggles and social issues that concerned Asians in Canada. The Asianadian established a national platform for then-emerging Asian-Canadian writers, artists, musicians, activists, and scholars like Sky Lee, Jim Wong-Chu, Joy Kogawa, Himani Bannerji, and Paul Yee. Columns like "On the Firing Line" and the "Dubious Achievement Awards" provided space to laugh back at the embarrassing concoction of Orientalist stereotypes in the media and to critique inconsistencies and superficialities within Canada's newfound multicultural image. Situating the story of The Asianadian within the history of Canada, Angie Wong celebrates and builds on the work of its creators from the Asianadian Resource Workshop. The extensive interview material with the co-founding members, editors, volunteers, readers, and contributors captures their dedication and spirit of anti-racist collectivism. Like the collective did before her, Wong's work helps to dismantle cultural assumptions that have relegated Asian Canadian history, contributions, and injustices to the periphery of Canadian experience and identity. On the heels of the COVID-19 pandemic and a resurgence of anti-Asian racism, Laughing Back at Empire amplifies the voices that speak, shout, and laugh together at empire's self-congratulatory and exclusionary narratives."-- Provided by publisher.
Keywords: Asianadian.; Canadian periodicals -- History -- 20th century.; Asians in mass media.; Social justice -- Canada -- Periodicals.; Asian Canadians -- Periodicals.; Asian Canadians -- Politics and government -- Periodicals.; Asian Canadians -- Social conditions -- Periodicals.; Asian Canadians -- Social life and customs -- Periodicals.; Périodiques canadiens -- Histoire -- 20e siècle.; Justice sociale -- Canada -- Périodiques.; Asians in mass media; Canadian periodicals; Social justice; Canada; 1900-1999; History; Periodicals